Pengaruh Reward dan Punishment Terhadap Kinerja Pegawai Kantor Kementerian Pertanian Direktorat Jenderal Peternakan dan Kesehatan Hewan - Vinni Widastari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Reward and punishment are two different things, but they are very important and interrelated because they have a role in making employees improve the quality of work and be more responsible for the tasks assigned. The purpose of this study was to determine the effect of reward and punishment on employee performance at the Office of the Ministry of Agriculture, Directorate General of Animal Husbandry and Animal Health. The population used was 250 employees. The sampling method in this study with random sampling technique using the slovin formula to 154 respondents. The research was conducted by distributing questionnaires to respondents using Likert scale measurements. The data analysis technique in this study uses validity test, reliability test, classical assumption test, multiple linear regression equation test and hypothesis testing. Based on the results of the research conducted, it can be concluded that reward and punishment have a positive effect on employee performance at Kementerian Pertanian Direktorat Jenderal Peternakan dan Kesehatan Hewan.